2019
DOI: 10.1093/cercor/bhz159
|View full text |Cite
|
Sign up to set email alerts
|

Linking Individual Movements to a Skilled Repertoire: Fast Modulation of Motor Synergies by Repetition of Stereotyped Movements

Abstract: Motor skills emerge when practicing individual movements enables the motor system to extract building instructions that facilitate the generation of future diverse movements. Here we asked how practicing stereotyped movements for minutes affects motor synergies that encode human motor skills acquired over years of training. Participants trained a kinematically highly constrained combined index-finger and thumb movement. Before and after training, finger movements were evoked at rest by transcranial magnetic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Also, the function of motor cortex in this synergistic control should be clarified. It was indeed shown that a synergistic structure of motor control may be coded in the primary motor cortex (Schieber and Santello, 2004;Ejaz et al, 2015;Leo et al, 2016;Fricke et al, 2020). Invasive cortical stimulation of monkeys further confirmed this phenomenon (Overduin et al, 2015), which nevertheless needs to be associated with how descending commands are organized at the spinal level.…”
Section: Discussionmentioning
confidence: 83%
“…Also, the function of motor cortex in this synergistic control should be clarified. It was indeed shown that a synergistic structure of motor control may be coded in the primary motor cortex (Schieber and Santello, 2004;Ejaz et al, 2015;Leo et al, 2016;Fricke et al, 2020). Invasive cortical stimulation of monkeys further confirmed this phenomenon (Overduin et al, 2015), which nevertheless needs to be associated with how descending commands are organized at the spinal level.…”
Section: Discussionmentioning
confidence: 83%
“…Kinematic information on finger movements was acquired by means of a glove in which flexion sensors were embedded. This technique is widely used to record finger dynamics (see, e.g., Gentner and Classen, 2006;Kumar et al, 2012;Cattaneo et al, 2015;Fricke et al, 2019), and instructions for its realization have been published by Gentner and Classen (2009). Three commercial righthand gloves of a stretchable grade of Lycra, of three different sizes (small, medium, and large hand size) were modified to accommodate four 114-mm-long flexion sensors (flexsensors 4.5 inch, Spectrasymbol) over the metacarpophalangeal and proximal interphalangeal joints of the thumb, index, and little fingers (1 sensor for each finger).…”
Section: Methodsmentioning
confidence: 99%
“…The literature on visually-guided grasp tells us that the peak aperture is already fully influenced by, and therefore informative of, the target size 30 . Similarly to previous investigation on fingers dynamics 37 40 , we measured MFE, by means of a custom-made glove made of a stretchable fabric of Lycra equipped with four flexible resistive bend sensors strategically placed to detect the voltage deriving from the extension of each finger involved in whole-hand grasps (Fig. 2 A).…”
Section: Methodsmentioning
confidence: 99%